IMIDACLOPRID TOXICITY ON BIOCHEMICAL CONSTITUENTS IN LIVER TISSUE OF FRESH WATER TELEOST CHANNA PUNCTATUS - B.PADMA PRIYA; Y.AVASN MARUTHI; Y.AVASN MARUTHI (International Journal of Pharma and Bio Sciences, 2013)
There is a lack of information regarding the alterations in liver metabolities induced by Imidacloprid Insecticide. In the present study, the fresh water teleost Channa punctatus (Bloch) were exposed to Imidacloprid Insecticide for 96h to assess the Biochemical constituents of Glycogen, Proteins, Lipids and Cholesterol of liver tissue. The liver tissue showed significant depletion of Glycogen, Protein and Lipids and significant increase of Cholesterol. In view of results, the present study reports metabolic dysfunction in response to Imidacloprid toxicity in the test fish.